Treatment of Medial Shoulder Joint Instability by Stabilization with an Arthroscopically Guided Prosthetic Ligament: A Cadaveric Feasibility Study in Dogs - Llido, Marie; Livet, Véronique; Carozzo, Claude; Viguier, Éric; Cachon, Thibaut (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to assess the feasibility and efficiency of an arthroscopically guided ligamentoplasty of the medial glenohumeral ligament to treat medial shoulder joint instability.Study Design Six Beagle cadavers were used (12 limbs). Both arms of the medial glenohumeral ligament were severed using arthroscopic guidance. Arthroscopically guided reconstruction of the ligament was performed. Threaded sutures were fixed with a bone anchor on the medial aspect of the glenoidal cavity of the scapula, passed through a humeral tunnel and finally tensioned with a suture button on lateral aspect of the humerus. Shoulder abduction angles were measured before and after the section of the medial glenohumeral ligament, and following the surgery. Two orthogonal radiographic projections and dissections were performed after each procedure to grade the placement of the implants.Results Surgical repairs were achieved in 10 out of 12 limbs. The abduction angles after repair with ligamentoplasty were not significantly different from the abduction angles measured before the section of the medial glenohumeral ligament.Conclusion Arthroscopically guided ligamentoplasty with a scapular bone anchor and a humeral drilling tunnel is feasible in cadavers, and efficient to restore acutely shoulder abduction angle in a minimally invasive manner. Further clinical studies are required to assess in vivo results.
Keywords: minimally-invasive surgery; ligamentoplasty; dog; medial shoulder instability; arthroscopy